2000
DOI: 10.1034/j.1600-0420.2000.078006689.x
|View full text |Cite
|
Sign up to set email alerts
|

Direct silicone intubation using Nunchaku‐style tube (NST‐DSI) to treat lacrimal passage obstruction

Abstract: ABSTRACT.Purpose: To confirm the usefulness of direct silicone intubation using a Nunchaku-style tube (NST-DSI) for the treatment of lacrimal passage obstruction. Methods: Included in this retrospective study were 54 cases (45 patients) of adult-onset lacrimal passage obstruction on which NST-DSI was performed. The cases were subdivided into two groups: 29 cases of common canalicular obstruction (the canalicular obstruction group) and 25 cases of nasolacrimal duct obstruction (the duct obstruction group). Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 6 publications
(12 reference statements)
1
32
0
Order By: Relevance
“…In CCO, silicone intubation is also used in treatments involving laser canaliculoplasty 17 and external DCR with membranectomy, 18 and a variety of silicone intubation sets have been described. 12,14,15,[24][25][26] The probes have blunt tips to avoid submucosal penetration and injury to the lacrimal mucosa; however, blind insertion is required. We revealed that conventional methods of tube insertion have a high associated risk of submucosal penetration (20%), 12 and a quarter of CCO cases have severe ductal stenosis, which makes blind intubation diffi cult.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In CCO, silicone intubation is also used in treatments involving laser canaliculoplasty 17 and external DCR with membranectomy, 18 and a variety of silicone intubation sets have been described. 12,14,15,[24][25][26] The probes have blunt tips to avoid submucosal penetration and injury to the lacrimal mucosa; however, blind insertion is required. We revealed that conventional methods of tube insertion have a high associated risk of submucosal penetration (20%), 12 and a quarter of CCO cases have severe ductal stenosis, which makes blind intubation diffi cult.…”
Section: Discussionmentioning
confidence: 99%
“…Nunchaku-style silicone tubes (NSTs) (Kaneka, Tokyo, Japan; Fig. 1) 14,15 were inserted using the EGT technique.…”
Section: Ei Inferior Meatal Dacryorhinotomy and Endonasal Dcrmentioning
confidence: 99%
“…In retrospective studies, the success rate of NST intubation (NSTI) for the treatment of nasolacrimal duct obstruction was reported to be between 68.0 and 87.5 %, and that of common canalicular obstruction between 75.9 and 89.5 % [11][12][13]. The findings of those reports suggest that NSTI could be used as an alternative to DCR in some cases.…”
Section: Introductionmentioning
confidence: 94%
“…Dacryocystorhinostomy (DCR) is a primary surgical pathway for the treatment of lacrimal drainage duct obstruction. However, due to the invasiveness of the procedure, (i.e., bone resection and general anesthesia when necessary), reconstructive surgery by silicone intubation (SI) has been employed as an alternative treatment method [1][2][3][4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%